2022
DOI: 10.3390/nu14061193
|View full text |Cite
|
Sign up to set email alerts
|

Today’s Mediterranean Diet in Greece: Findings from the National Health and Nutrition Survey—HYDRIA (2013–2014)

Abstract: Background: This study aimed to investigate the food and macronutrient intake of the population in Greece and evaluate its adherence to the Greek traditional Mediterranean diet. Methods: Adults over 18 years old (n = 4011) were included from the 2013–2014 National Health and Nutrition survey—HYDRIA. Dietary intake was collected using two 24-h recall interviews and a nonquantitative food frequency questionnaire. Macronutrient intakes were calculated using an updated version of the Greek FCT. Results: Only 28.3%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 47 publications
4
35
0
Order By: Relevance
“…Key elements of the findings provide important insights. Significantly, it was found that the contribution of total fat in adults was higher than the 20–35% of dietary reference intake ranges suggested by EFSA ( 11 ). In both men and women, 42–43% of total energy intake was from fat.…”
Section: Greek National Health and Nutrition Survey -Hydria And Dieta...mentioning
confidence: 70%
See 2 more Smart Citations
“…Key elements of the findings provide important insights. Significantly, it was found that the contribution of total fat in adults was higher than the 20–35% of dietary reference intake ranges suggested by EFSA ( 11 ). In both men and women, 42–43% of total energy intake was from fat.…”
Section: Greek National Health and Nutrition Survey -Hydria And Dieta...mentioning
confidence: 70%
“…A higher MUFA percentage of total energy intake was noted for those individuals above 65 years of age at 21.9–21.3 vs. 20.1% for the younger adults surveyed. The high consumption of monounsaturated fats from olive oil was the main contributor of overall fat intake, with median distribution of the usual daily intake from fats and oils being 44 g for men and 32 g for women overall, with olive oil alone representing 34 g and 25 g for men and women, respectively ( 11 ).…”
Section: Greek National Health and Nutrition Survey -Hydria And Dieta...mentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors associate such discrepancies with the dissemination and increased popularity of the Western-type dietary pattern worldwide [ 51 , 57 ]. A recent report by Martimianaki et al, 2022 [ 58 ], signifies that only 28.3% of the Greek adult population have high adherence to the Greek traditional Mediterranean diet, most of which results from higher adherence (39.7%) by participants of 65 years or older. Younger individuals were more adherent to a Western diet pattern characterized by the consumption of red meat, animal fats, and cheese, with only 25.5% adherence to the Mediterranean diet.…”
Section: Role Of Diet and Physical Activitymentioning
confidence: 99%
“…This shift in dietary habits is the result of the nutritional transition phenomenon, i.e., the gradual abandonment of traditional dietary habits and practices due to urbanization, increasing affluence and the progressive globalization of food supply [ 16 ]. Epidemiological data have shown low rates of and decreasing trends in the level of adherence to the Mediterranean diet in typical Mediterranean countries, including Greece [ 17 , 18 , 19 ], Spain [ 20 , 21 , 22 ], Portugal [ 23 , 24 , 25 ] and Italy [ 26 , 27 , 28 ], especially in younger individuals and population groups of low socioeconomic status. A decreasing adherence to the Mediterranean diet is parallel to an increasing adoption of a Western-type dietary pattern, characterized by high intakes of pre-packaged foods, refined grains, processed meat, sugar-sweetened beverages, sweets and other highly-processed energy-dense foods rich in salt, sugars and saturated fat; indicatively, mean global Western Diet Similarity Index (computed as the proportion of per-capita total calories from animal source foods plus oils and fats from plant sources and sweeteners) has increased from 40.57 ± 17.15 in 1993 to 42.24 ± 16.04 in 2013 [ 29 ].…”
Section: Introductionmentioning
confidence: 99%